Luhansk (Donbas): Religious Freedom Survey, February 2022 - Corley, Felix (Occasional papers on religion in Eastern Europe, 2022)
Freedom of religion and belief is severely restricted in the rebel Luhansk People's Republic occupying currently (February 2022) about a third of Ukraine's Luhansk Region. Forum 18's survey analysis documents violations including: rendering illegal all Protestant and non-Moscow Patriarchate Orthodox communities; a climate of fear about discussing human rights violations; repeated denials of permission to a Roman Catholic priest to live in the region; and increasing numbers of banned allegedly "extremist" books, including an edition of the Gospel of John published in 1820. All human rights including the freedom of religion and belief are severely restricted in the rebel self-declared Luhansk People's Republic (LPR), which currently (February 2022) controls about a third of Ukraine's Luhansk Region. Among the rebels' violations documented by Forum 18 are: - a restrictive 2018 LPR Religion Law which imposed re-registration of religious communities which were already registered under Ukrainian law, as well as making illegal any religious community which did not gain rebel permission to exist. This resulted in all Protestant and non-Moscow Patriarchate Orthodox communities being denied rebel permission to exist; - punishments for meeting for worship without rebel permission; - the banning by the State Security Ministry (SSM) secret police of all Ukrainian Baptist Union communities, despite this being illegal under LPR law as no court order was apparently made; - repeated raids on places of worship and unregistered religious communities being denied access to any buildings they own; - social welfare activities carried out by unregistered religious communities being stopped; - surveillance of local religious communities, and the encouragement by LPR rebels of a climate of fear about discussing human rights violations; - cutting off gas, water, and electricity supplies to all places of worship owned by unregistered communities; - contacts with fellow believers of any faith elsewhere in Ukraine being made difficult or impossible, including repeated denials of permission to a Catholic priest resident in Luhansk since 1993 to continue to live in the region, as well as to nuns to return to a parish. This has resulted in the repeated inability of Catholics to receive Communion at Mass, a central part of the Catholic faith; - and an increasing list of banned allegedly "extremist" books, including an edition of the Gospel of John originally published in 1820.